Uji Kadar Likopen dan Aktivitas Antioksidan pada Buah Tomat - Fanny Mariska Sima; Esther Majawati; Hendrik Kurniawan (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2019)
Oxidative stress, a condition of imbalanced free radicals and antioxidant in our body has long been associated with the occurrence of atherosclerosis, inflammation, cancer, and aging. Increased oxidative stress, due to high fat intake and pollution requires the consumption of antioxidant compounds from food or food supplements. Tomatoes (Solanum lycopersicum) has been known to have a high content of lycopene that is capable of controlling free radicals 100 times more efficiently than vitamin E and 12500 times than glutathione peroxidase which is an endogenous antioxidant enzyme. The purpose of this study was to determine lycopene content and antioxidant activity of tomatoes. Antioxidant activity was determined spectrophotometrically based on a DPPH method, whereas lycopene content was determined based on its absorbance and its specific absorbance. This study found that the IC50 of tomatoes was 60 µg/ml which is classified as strong antioxidant, and lycopene content in tomatoes was 3.42 mg / kg fresh sample. Therefore, this study may conclude tomatoes as a good source of antioxidant.